Optimizing the AC Operation for Energy Management and AC Failure Monitoring System Through GSM Technology for School Bus - et. al., Vanitha Mahadevan, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper presents an ideology of optimizing the energy consumption through the controlled operation of Air conditioning system in school bus or any transport system. This includes two concepts, one is on/off the AC by measuring the temperature inside the bus and the second is in case of any failure of AC in the bus, informing the condition to the maintenance people. The main devices used are Arduino, temperature sensor (DS18B20) and SIM900. The temperature sensor used to sense the temperature and send the signal to Arduino. Based upon the temperature value the Arduino will operate the relay to turn on/off the AC. If the temperature is keep on increasing beyond the predefined value, then the AC is not working. This information will be send to the mobile number of maintenance team in charge.